Extremophilic Prokaryotic Endoxylanases: Diversity, Applicability, and Molecular Insights - Verma, Digvijay (Frontiers in Microbiology, 2021)
Extremophilic endoxylanases grabbed attention in recent years due to their applicability under harsh conditions of several industrial processes. Thermophilic, alkaliphilic, and acidophilic endoxylanases found their employability in bio-bleaching of paper pulp, bioconversion of lignocellulosic biomass into xylooligosaccharides, bioethanol production, and improving the nutritious value of bread and other bakery products. Xylanases obtained from extremophilic bacteria and archaea are considered better than fungal sources for several reasons. For example, enzymatic activity under broad pH and temperature range, low molecular weight, cellulase-free activity, and longer stability under extreme conditions of prokaryotic derived xylanases make them a good choice. In addition, a short life span, easy cultivation/harvesting methods, higher yield, and rapid DNA manipulations of bacterial and archaeal cells further reduces the overall cost of the product. This review focuses on the diversity of prokaryotic endoxylanases, their characteristics, and their functional attributes. Besides, the molecular mechanisms of their extreme behavior have also been presented here.